Multi-Objective Mixed Integer Linear Programming Model for Energy Resource Allocation Problem: The Case of Turkey - Erol,Serpil; Özcan,Evren Can (Gazi University Journal of Science, 2014)
Energy is one of the most basic elements for raising social welfare, playing a fascinating role in economic and social progress of the countries and thus increasing the competitiveness of the countries in globalized world. Therefore, carrying out the sustainable energy policies which are based on social, economic and environmental factors and in this context, finding the local, sustainable, environmentally-friendly and economic resources and the optimal distribution of them have become a necessity in order to achieve the sustainable development thrusts. In this study, a multi-objective mixed integer linear programming (MOMILP) model which reflects the Turkey’s realities and necessities and optimizes simultaneously the objectives of total cost minimization, CO2 emission minimization, energy import minimization, fossil resource usage minimization, employment maximization and social acceptance maximization is proposed. This model is solved by Minimum Deviation Method (MDM) considering the most basic energy resources (solar, wind, coal, natural gas, hydroelectric, nuclear etc.) used for the electricity generation all over the world and a 11-years electricity generation plan is obtained on the basis of resources for Turkey.